2016
DOI: 10.1002/ejic.201501272
|View full text |Cite
|
Sign up to set email alerts
|

Hydroelementation of Unsaturated C–C Bonds Catalyzed by Metal Scorpionate Complexes

Abstract: Tridentate scorpionate ligands have a rich history in coordination chemistry. In the past two decades, metal complexes bearing scorpionate ligands have found increasing utility as catalysts for a variety of useful transformations. This microreview focuses on the utility of scorpionate ligands in hydro- [a] 2396 Scheme 13. Proposed mechanism for To M Mg-mediated aminoalkene hydroamination (see ref. [54] ).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 123 publications
0
12
0
Order By: Relevance
“…Intramolecular hydrophosphination of alkynes catalyzed by trivalent lanthanides was reported 15 years ago by Marks et al The first intermolecular version using divalent lanthanides followed soon thereafter . Ever since, there is an increasing interest in the hydrophosphination catalyzed by di- and trivalent lanthanide complexes. The recent development was covered by some review articles. …”
Section: Introductionmentioning
confidence: 99%
“…Intramolecular hydrophosphination of alkynes catalyzed by trivalent lanthanides was reported 15 years ago by Marks et al The first intermolecular version using divalent lanthanides followed soon thereafter . Ever since, there is an increasing interest in the hydrophosphination catalyzed by di- and trivalent lanthanide complexes. The recent development was covered by some review articles. …”
Section: Introductionmentioning
confidence: 99%
“…magnets. 10,11,12 Other promising application fields of pyrazolylborate complexes are catalysis 13,14,15,16,17 and the incorporation into polymers, 18 dendrimers, 19 molecular machines, 20 and metal-organic frameworks. 21 From the very first, these compounds have been studied by using paramagnetic NMR spectroscopy (pNMR) 1,22,23,24 and the initial results have been compiled.…”
mentioning
confidence: 99%
“…Transition metal‐catalyzed reactions involving nitrene transfer to alkenes have gained prominence in this regard , . Of these latter catalysts, copper(I) and silver(I) scorpionate complexes [tris(pyrazolyl)borates, (normal scorpionates, or Tp R , Scheme , top left), tris(pyrazolyl)methanes (Tpm R or C ‐scorpionates, Scheme , top right), certain C‐heteroscorpionates (Scheme , bottom left), and certain nitrogen‐confused C‐scorpionates (Scheme , bottom right)] have proven adept at catalytically affording aziridines from alkenes and various nitrene sources under mild conditions. Thus, Pérez and co‐workers found that Tp*Cu(C 2 H 4 ), or other CuTp R complexes (prepared in‐situ) catalyze the aziridination of styrene, cyclooctene, or 1‐hexene over the course of a few hours at room temperature in CH 2 Cl 2 using PhI=NTs as a nitrene transfer agent.…”
Section: Introductionmentioning
confidence: 99%